A Novel Perylene Polymer Based on the 1,3,5-Triazines - Dinleyici, Meltem (Eastern Mediterranean University EMU, 2015)
Perylene chromophore containing supramolecular chromogenic polymers represent an important research topic relating to its interesting optoelectronic and redox properties. In the present study, a novel chromogenic polymer (TAPPI) was synthesized by polycondensation of perylene-3,4,9,10-tetracarboxylic dianhydride (PDA) with hindered aromatic diamine, 2,4-diamino-6-phenyl-1,3,5-triazine in isoquinoline and m-cresol solvents mixture under argon atmosphere. The synthesized product purity was confirmed using elemental analysis, IR and UV-vis spectroscopy. The product TAPDI is soluble mainly in polar solvents such as pyridine, NMP, DMF, DMSO, m-cresol in purple and TFAc pink colours. It is important to note that, different absorption and emission properties have been observed due to different intermolecular interactions in various solvents. The lower fluorescence quantum yield of the TAPPI in NMP, DMF and DMSO solvents (70%, 60% and 30%) could be attributed to conformational changes, torsional movement, or other non-radiative decays. Overall, the new polymer TAPPI has shown great potential for further photonic technology. Keywords: Perylene polymers, hindered diamine, photonics, solar cells.

ÖZ: Perilen kromoforları ihtiva eden süpramoleküler ve kromojenik polimerler ilginç optoelektronik ve redoks özellikleri nedeniyle önemle araştırılmaktadırlar. Bu çalışmada yeni bir perilen polimeri (TAPPI), perilen-3,4,9,10-tetrakarboksilik dianhidrit (PDA) ve engelli aromatik diamin, 2,4-diamino-6-fenil-1,3,5-triazine polikondensasyon reaksiyonu ile isokinolin ve m-kresol çözgenleri karışımında ve argon ortamında sentezlenmiştir. Elde edilen ürünün saflığı elemental analiz, IR ve UV-vis spektroskopileri ile doğrulanmıştır. TAPPI polimeri özellikle piridin, NMP, DMF, DMSO, m-kresol içerisinde mor ve TFAc‟de ise pembe renkte çözünmektedir. Moleküller arası farklı ilişkilere bağlı olarak gözlemlenen farklı absorpsiyon ve emisyon özellikleri fotonik cihazlarda uygulamalar açısından önemlidir. NMP, DMF and DMSO çözgenlerinde ölçülen fluoresans kuantum verimlerin düşük olmasının (sırasıyle; 70%, 60% ve 30%) konformasyon değişimleri, torsiyon hareketleri ve diğer ışınımsız geçişlerle bağlı olduğu düşünülmektedir. Genel itibariyle, sentezlenmiş olan yeni perilen polimerinin fotonik uygulamalar için büyük potansiyele sahip olduğu saptanmıştır. Anahtar kelimeler: Perilen polimerleri, engelli diamin, fotonik, solar hücreler.
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2015. Supervisor: Prof. Dr. Huriye İcil.
Keywords: Chemistry; Perylene polymers; hindered diamine; photonics; solar cells